Lymphoscintigraphic alterations in lower limbs in women with lipedema in comparison to women with overweight/obesity - Chachaj, Angelika; Dudka, Ilona; Jeziorek, Małgorzata; Sowicz, Monika; Adaszyńska, Agnieszka; Szuba, Andrzej (Frontiers in Physiology, 2023)
Lipedema is a bilateral enlargement of the legs due to abnormal depositions of subcutaneous fat. Recent studies using lymphoscintigraphy documented that lipedema associates with lymphatic alterations. It is still not known, whether non-lipedema obesity also leads to similar lymphoscintigraphic changes within lower legs. Clinically, both, lipedema and obesity may progress to secondary lymphedema. The aim of the study was to evaluate lymphoscintigraphy of lower limbs in women with lipedema in comparison to overweight/obese women. 51 women (in the mean age of 43.3 ± 13.56) with the diagnosis of lipedema and 31 women (in the mean age of 44.7 ± 13.48) with overweight/obesity were enrolled into the study. Women in both study groups had no clinical signs of lymphedema. The groups were matched by mean volume of their legs, calculated using the formula for a truncated cone. Lymphoscintigraphy was evaluated in every women qualitatively. Body composition parameters were assessed using bioelectric impedance analysis (BIA). Lymphoscintigraphic alterations within lower extremities were similar in both lipedema and overweight/obese groups and were present in majority of women in both study groups. The most common lymphoscintigraphic alteration in both groups were additional lymphatic vessels (in the lipedema group observed in 76.5% of patients and in the overweight/obesity group – in 93.5%). Visualization of popliteal lymph nodes and dermal backflow were observed respectively in 33% and in 5.9% in the group with lipedema and in 45.2% and in 9.7% in the overweight/obesity group. There were significant relationships between severity of lymphoscintigraphic alterations and weight, lean body mass (LBM), total body water (TBW), volume of both legs and thigh circumference in the lipedema group. Such relationships were absent in the overweight/obesity group. Our study indicates that lymphatic alterations are present before development to clinically visible secondary lymphedema in both conditions, lipedema and overweight/obesity. In majority of women from both study groups they indicate rather an overload of the lymphatic system then insufficiency. Lymphoscintigraphic alterations are similar in both groups, therefore, lymphoscintigraphy is not a diagnostic tool that might distinguish lipedema from overweight/obesity.